Optical eye tracking system for real‐time noninvasive tumor localization in external beam radiotherapy. Issue 5 (10th April 2015) - Via, Riccardo; Fassi, Aurora; Fattori, Giovanni; Fontana, Giulia; Pella, Andrea; Tagaste, Barbara; Riboldi, Marco; Ciocca, Mario; Orecchia, Roberto; Baroni, Guido
Abstract : Purpose: External beam radiotherapy currently represents an important therapeutic strategy for the treatment of intraocular tumors. Accurate target localization and efficient compensation of involuntary eye movements are crucial to avoid deviations in dose distribution with respect to the treatment plan. This paper describes an eye tracking system (ETS) based on noninvasive infrared video imaging. The system was designed for capturing the tridimensional (3D) ocular motion and provides an on‐line estimation of intraocular lesions position based on a priori knowledge coming from volumetric imaging. Methods: Eye tracking is performed by localizing cornea and pupil centers on stereo images captured by two calibrated video cameras, exploiting eye reflections produced by infrared illumination. Additionally, torsional eye movements are detected by template matching in the iris region of eye images. This information allows estimating the 3D position and orientation of the eye by means of an eye local reference system. By combining ETS measurements with volumetric imaging for treatment planning [computed tomography (CT) and magnetic resonance (MR)], one is able to map the position of the lesion to be treated in local eye coordinates, thus enabling real‐time tumor referencing during treatment setup and irradiation. Experimental tests on an eye phantom and seven healthy subjects were performed to assess ETS tracking accuracy. Results: Measurements on phantom showed an overall median accuracy within 0.16 mm and 0.40° for translations and rotations, respectively. Torsional movements were affected by 0.28° median uncertainty. On healthy subjects, the gaze direction error ranged between 0.19° and 0.82° at a median working distance of 29 cm. The median processing time of the eye tracking algorithm was 18.60 ms, thus allowing eye monitoring up to 50 Hz. Conclusions: A noninvasive ETS prototype was designed to perform real‐time target localization and eye movement monitoring during ocular radiotherapy treatments. The device aims at improving state‐of‐the‐art invasive procedures based on surgical implantation of radiopaque clips and repeated acquisition of X‐ray images, with expected positive effects on treatment quality and patient outcome.